Characteristics of inflammatory bowel disease in patients of Roma/Gypsy ethnicity. A case-control study. Issue 5 (May 2019) - Cabré, Eduard; Mañosa, Míriam; Marín, Ignacio; Martín-Mateos, Rosa; Iglesias-Flores, Eva; Barreiro-de-Acosta, Manuel; Nos, Pilar; Busquets, David; Menchén, Luis A.; López-Sanromán, Antonio; Domènech, Eugeni
Abstract: Background: Peculiarities of inflammatory bowel disease (IBD) have been explored in ethnic groups, such as Asians, Hispanics, and Afro-Americans, but not in other ethnic minorities, such as Roma/Gypsies. Methods: In a retrospective, hospital-based study, all adult Roma/Gypsy patients included in the IBD databases of seven Spanish centres were identified as cases. For each Roma/Gypsy patient, a Caucasian patient, matched for several demographic features, was searched as a control. Data on phenotypic features, therapeutic requirements, and familial aggregation were recorded. Results: Sixty-eight Roma/Gypsy patients were identified, 29 of them being women. The mean age at diagnosis of IBD was 24.9 ± 9.5 years, and the mean time elapsed since diagnosis was 96.6 ± 72.2 months. Roma/Gypsy IBD patients showed a significantly higher rate of familial aggregation (43%) than their Caucasian controls (9%) (p = 0.00001). CD in Roma/Gypsies had more often a complicated pattern (mainly penetrating) while UC patients showed a marked trend to more often developing extraintestinal manifestations. In addition, Roma/Gypsy IBD patients had a somewhat greater need for immunosuppressants, biological agents or surgery. Conclusions: These are the first data on IBD in Roma/Gypsy patients. Familial aggregation is the most prominent feature in these patients, suggesting a predominant role of genetics in its pathogenesis.